Crystal growth and characterisation of a unique trinuclear VIV/VV complex - Chimupala Y. (2014)
Single crystals of a mixed-valence trinuclear cluster of formula [V2VVIVO5(C12H8N2)3(SO4)2(H2O)3].6H2O were grown by layer diffusion technique and characterised by single-crystal X-ray diffraction; P21/c, a = 20.5448(11) Å, b = 11.7647(9) Å, c = 18.1871(9) Å, β = 92.64(0)°, V = 4391.22 (93) Å3, R = 0.0941 and Rw = 0.1345. A distinct characteristic of the structure is the existence of the rare linear mono-μ-oxo [V2VVIVO5]4+ building units and the presence of a large number of hydrogen bonds and π-π interactions. The study on the mixed valence state of vanadium by valence bond sum calculations, manganometric titration and cyclic voltammetry, and the presence of π-π interactions by calculation of the harmonic oscillator model of aromaticity indices are presented. The thermogravimetric and differential scanning calorimetric analysis is also reported. The results of UV-Vis spectroscopic study and band gap energy calculation are included. © 2011 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.